2017
DOI: 10.1590/1413-70542017414047716
|View full text |Cite
|
Sign up to set email alerts
|

Externally studentized normal midrange distribution

Abstract: The distribution of externally studentized midrange was created based on the original studentization procedures of Student and was inspired in the distribution of the externally studentized range. The large use of the externally studentized range in multiple comparisons was also a motivation for developing this new distribution. This work aimed to derive analytic equations to distribution of the externally studentized midrange, obtaining the cumulative distribution, probability density and quantile functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…is the sample midrange and S is an estimator of the population standard deviation with ν degrees of freedom and independent of R . Batista, Ferreira and Chaves (2017) showed the distribution and density functions of Q from Equation 1. However, they also showed that the Q statistic is not an ancillary statistic, making it difficult to develop new tests based on this statistic.…”
Section: Introductionmentioning
confidence: 99%
“…is the sample midrange and S is an estimator of the population standard deviation with ν degrees of freedom and independent of R . Batista, Ferreira and Chaves (2017) showed the distribution and density functions of Q from Equation 1. However, they also showed that the Q statistic is not an ancillary statistic, making it difficult to develop new tests based on this statistic.…”
Section: Introductionmentioning
confidence: 99%